Reduced Plasma Extracellular Vesicle CD5L Content in Patients With Acute-On-Chronic Liver Failure: Interplay With Specialized Pro-Resolving Lipid Mediators - Sánchez-Rodríguez, María Belen; Téllez, Érica; Casulleras, Mireia; Borràs, Francesc E.; Arroyo, Vicente; Clària, Joan; Sarrias, Maria-Rosa (Frontiers in Immunology, 2022)
Acute-on chronic liver failure (ACLF) is a syndrome that develops in patients with acutely decompensated cirrhosis (AD). It is characterized by a systemic hyperinflammatory state, leading to multiple organ failure. Our objective was to analyze macrophage anti-inflammatory protein CD5L in plasma extracellular vesicles (EVs) and assess its as yet unknown relationship with lipid mediators in ACLF. With this aim, EVs were purified by size exclusion chromatography from the plasma of healthy subjects (HS) (n=6) and patients with compensated cirrhosis (CC) (n=6), AD (n=11) and ACLF (n=11), which were defined as positive for CD9, CD5L and CD63 and their size, number, morphology and lipid mediator content were characterized by NTA, EM, and LC-MS/MS, respectively. Additionally, plasma CD5L was quantified by ELISA in 10 HS, 20 CC and 149 AD patients (69 ACLF). Moreover, macrophage CD5L expression and the biosynthesis of specialized lipid mediators (SPMs) were characterized in vitro in primary cells. Our results indicate that circulating EVs were significantly suppressed in cirrhosis, regardless of severity, and showed considerable alterations in CD5L and lipid mediator content as the disease progressed. In AD, levels of EV CD5L correlated best with those of the SPM RvE1. Analysis of total plasma supported these data and showed that, in ACLF, low CD5L levels were associated with circulatory (p<0.001), brain (p<0.008) and respiratory (p<0.05) failure (Mann-Whitney test). Functional studies in macrophages indicated a positive feedback loop between CD5L and RvE1 biosynthesis. In summary, we have determined a significant alteration of circulating EV contents in ACLF, with a loss of anti-inflammatory and pro-resolving molecules involved in the control of acute inflammation in this condition.